2014
DOI: 10.1038/eye.2014.294
|View full text |Cite
|
Sign up to set email alerts
|

Surgical outcome of safe surgery system trabeculectomy combined with cataract extraction

Abstract: Purpose To determine the efficacy of safe surgery system trabeculectomy combined with manual small incision cataract surgery/ phacoemulsification in primary glaucoma coexistent with cataract. Methods This is a retrospective analysis of 105 cases who underwent single-site combined surgery between January 2008 and December 2009. Safe surgery system trabeculectomy with diffuse and posterior application of mitomycin C was performed in all cases. Cataract extraction was done either by Manual Small Incision Cataract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
1
2
0
1
Order By: Relevance
“…For IOP ≤21 mmHg, the overall success was 80.5% in the study group and 90.9% for the control group, similar to earlier studies 14,2224. However when more stringent criteria of IOP ≤18 mmHg, was used, it was found that the overall success was only 36.6% for the study group and 68.2% for the control group.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…For IOP ≤21 mmHg, the overall success was 80.5% in the study group and 90.9% for the control group, similar to earlier studies 14,2224. However when more stringent criteria of IOP ≤18 mmHg, was used, it was found that the overall success was only 36.6% for the study group and 68.2% for the control group.…”
Section: Discussionsupporting
confidence: 85%
“…The IOP reduction was 31.3% in the study group (1-minute), as compared to 43.3% in the control group (2-minutes). Mittal et al14 found a mean IOP reduction of 31% in a retrospective analysis of combined surgery cases using MMC for 2 minutes, and Khandelwal et al 24 found a 40% reduction with MMC for 2 minutes in combined surgery cases after 12 months follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We reviewed seven retrospective studies comparing (a) Manual small-incision cataract surgery with trabeculectomy (n = 352 eyes) and (b) Phacoemulsification with trabeculectomy (n = 348) eyes [12][13][14][15][16][17][18]. No prospective studies were found from the study selection process.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Die während der Kataraktoperation durchgeführte Gabe von 5-Fluorouracil subkonjunktival kann zwar das Risiko der Druckentgleisung mindern, aber nicht ganz verhindern [44,45]. Aus diesem Grunde gibt es auch gute Argumente, zusammen mit der filtrierenden Operation auch gleichzeitig eine Kataraktoperation durchzuführen, insbesondere wenn schon eine beginnende Katarakt vorhanden ist, deren rasche Progression nach einer alleinigen filtrierende Operation quasi sicher ist [46][47][48]. Das Hauptargument, dass die kombinierten Katarakt-/Glaukomoperationen bez.…”
Section: Wann Muss Ein Glaukompatient Operiert Werden?unclassified